2010
DOI: 10.1097/mop.0b013e328336eb85
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of bronchopulmonary dysplasia in the age of genomics

Abstract: Purpose of review-According to recent evidence, susceptibility to bronchopulmonary dysplasia (BPD) in preterm infants is predominantly inherited. The purpose of this review is to discuss current published genetic association studies in light of the accumulated knowledge in genomics.Recent findings-Major advances in the development of next generation genotyping and sequencing platforms, statistical methodologies, inventories of functional outcome of some common genetic polymorphisms and large scale cataloguing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 57 publications
0
39
0
1
Order By: Relevance
“…Twin studies have shown that even after controlling for covariates, genetic factors account for 53% of the variance in susceptibility to BPD (3). In the past, components of the innate immune system and antioxidant defenses, mechanisms of vascular and lung remodeling, and surfactant proteins have been the focus of genetic-association studies in BPD (4,5). Candidate genes for further research have been identified in these studies; however, any particular gene or gene pathway was not concluded to have a substantial contribution to the underlying etiology of BPD (5).…”
mentioning
confidence: 99%
“…Twin studies have shown that even after controlling for covariates, genetic factors account for 53% of the variance in susceptibility to BPD (3). In the past, components of the innate immune system and antioxidant defenses, mechanisms of vascular and lung remodeling, and surfactant proteins have been the focus of genetic-association studies in BPD (4,5). Candidate genes for further research have been identified in these studies; however, any particular gene or gene pathway was not concluded to have a substantial contribution to the underlying etiology of BPD (5).…”
mentioning
confidence: 99%
“…Genetic susceptibility (17,49,67) and environmental factors have all been implicated in the etiology of BPD (3,12). Inflammation and trauma at critical stages of lung development lead to dysmorphic lung tissue with impaired functionality (12,33,47).…”
mentioning
confidence: 99%
“…5 Early gestational age is the greatest risk factor for BPD development; however, recent studies indicate that genetic polymorphisms may influence development and severity of BPD. 6,7 Abman and colleagues have suggested that genetic susceptibility for BPD development may be similar to that of other complex diseases such as systemic hypertension and psychiatric illnesses. In utero and postnatal exposures can also influence development and severity of BPD.…”
Section: Introductionmentioning
confidence: 96%